Taking Back Control: A Bank’s perspective into the use of risk control systems of investment re-allocation and their resiliency under random CTA performance. - Leon Gambetta Johanson, Jose Antonio (2016)
This study was done with the purpose of making trading investments more attractive to a Bank. We Identify a disconnect between the investor (Bank) and the Trader (CTA). CTA’s are often regarded as long-term investment options and are assumed to prefer a fixed amount of capital with which to work with. From a Bank’s perspective, handing over 100% of the investment risk to the Trader not only exposes its investment to market risk, but also operational risk via the Trader. Therefore, we propose the idea of taking back control of the investment, by managing the funds available to the Trader based on his performance.